Novel chromium-free self-lubricating anticorrosive aluminum coating as well as preparation method and application thereof

By preparing a new type of chromium-free self-lubricating anti-corrosion aluminum coating, the galvanic corrosion and hydrogen embrittlement problems of titanium alloy fasteners are solved, environmentally friendly and efficient anti-corrosion and self-lubricating properties are achieved, and the service life and reliability of the fasteners are improved.

CN120699500APending Publication Date: 2025-09-26LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510841959.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing titanium alloy fasteners have galvanic corrosion problems in the aviation field. Traditional electroplating treatment has problems of environmental pollution and complex process. In addition, titanium alloy fasteners are prone to galvanic corrosion when combined with aluminum materials, affecting corrosion resistance and appearance quality. At the same time, hydrogen embrittlement reduces mechanical properties, and cadmium plating treatment is restricted by environmental regulations.

Method used

A new type of chromium-free self-lubricating anti-corrosion aluminum coating is used, including boron-modified phenolic resin, epoxy resin, lubricant, wear-resistant agent, moisture absorbent, aluminum powder and other components. It is prepared by mixing and grinding in a special proportion to form a self-lubricating anti-corrosion aluminum coating, which is applied to the surface of fasteners.

Benefits of technology

It achieves environmentally friendly self-lubricating and anti-corrosion properties, improves the service life and reliability of fasteners, enhances the density and hardness of the coating, meets the environmental protection requirements of the aviation field, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699500A_ABST
    Figure CN120699500A_ABST
Patent Text Reader

Abstract

The invention provides a novel chromium-free self-lubricating anti-corrosion aluminum coating as well as a preparation method and application thereof. The aluminum coating comprises the following components in percentage by weight: 20-40% of boron modified phenolic resin, 1-6% of epoxy resin, 7-30% of a lubricant, 5-10% of a wear-resistant agent, 2-5% of a moisture absorbent, 5-20% of aluminum powder, 2-5% of a thixotropic agent, 5-10% of an anticorrosive filler, 0.5-1.5% of an adhesion promoter, 1-2% of an anti-settling agent, 1-2% of a dispersant, 2-8% of a flexibilizer and the balance of an organic solvent, wherein the organic solvent comprises ethanol and butanone in a weight ratio of 1: (1-2). The aluminum coating is applied to preparation of a self-lubricating anti-corrosion aluminum coating on the surface of a fastener. According to the method, preparation of the chromium-free self-lubricating anti-corrosion aluminum coating and the aluminum coating is achieved, and the corrosion resistance and the assembly efficiency of aviation fasteners are greatly improved through the anti-corrosion and self-lubricating performance of the aluminum coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of anti-corrosion coatings, and in particular to a novel chromium-free self-lubricating anti-corrosion aluminum coating, a preparation method thereof, and an application thereof. Background Art

[0002] As key components in aircraft structures, aviation fasteners perform connecting and securing functions, and their performance and reliability are directly linked to aircraft safety and lifespan. Titanium alloy fasteners are widely used in aviation due to their light weight, high strength, fatigue resistance, and excellent corrosion resistance. However, aircraft often operate in complex and variable corrosive environments with high salt spray and high humidity. When titanium alloy fasteners are used in conjunction with aluminum, the high potential difference between the two materials, leading to galvanic corrosion, is a particularly prominent issue.

[0003] While traditional electroplating treatments have some effectiveness, they pose environmental risks and complex processes. Titanium alloy fasteners have complex structures and may contain hard-to-reach corners and crevices. This can lead to uneven coating during the cadmium plating process, resulting in patchy or missed plating areas, which compromise the fastener's corrosion resistance and appearance. Furthermore, titanium alloys can absorb hydrogen during the electroplating process, causing hydrogen embrittlement. Hydrogen embrittlement can reduce the mechanical properties and corrosion resistance of titanium alloy fasteners and increase the risk of fracture. Furthermore, the electroplating process can generate pollutants such as wastewater and exhaust gases, which have a certain impact on the environment. With increasingly stringent environmental regulations, cadmium plating of titanium alloy fasteners is increasingly restricted. Currently, the best protective method for titanium alloy fasteners is to apply an aluminum coating. Hi-Shear's Hi-Kotel series aluminum coatings are a prime example. They offer excellent adhesion, lubricity, and wear resistance, significantly improving the corrosion resistance and service life of titanium alloy fasteners. However, the use of Hi-Kotel series aluminum coatings in my country is both costly and faces the risk of supply disruptions, posing a threat to national defense and security.

[0004] Therefore, the development of a new type of aluminum coating that has both excellent anti-corrosion properties and self-lubricating and wear-resistant functions is of great significance to improving the reliability and extending the service life of aviation fasteners. Summary of the Invention

[0005] This application provides a novel chromium-free self-lubricating anti-corrosion aluminum coating and its preparation method and application, which are used to solve the above-mentioned problems mentioned in the background technology, overcome and eliminate the carcinogenic effect of chromate on the human body and the harm to the ecological environment.

[0006] The present application provides a novel chromium-free self-lubricating anti-corrosion aluminum coating, which comprises the following components in percentage by weight: Boron-modified phenolic resin 20-40%, epoxy resin 1-6%, lubricant 7-30%, anti-wear agent 5-10%, moisture absorbent 2-5%, aluminum powder 5-20%, thixotropic agent 2-5%, anti-corrosion filler 5-10%, adhesion promoter 0.5-1.5%, anti-settling agent 1-2%, dispersant 1-2%, toughening agent 2-8%, balance organic solvent; The organic solvent includes ethanol and butanone in a weight ratio of 1:1-2.

[0007] Optionally, the lubricant includes molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 2-10:5-20.

[0008] Optionally, the anti-wear agent is selected from Al2O3.

[0009] Optionally, the desiccant is acetic acid.

[0010] Optionally, the aluminum powder includes flake aluminum powder and spherical aluminum powder with a fineness of ≤10 μm, and the weight ratio of the flake aluminum powder to the spherical aluminum powder is 1:1-1.5.

[0011] Optionally, the anti-corrosion filler includes one or more of aluminum tripolyphosphate, aluminum dihydrogen tripolyphosphate and zinc phosphate.

[0012] On the other hand, the present application provides a method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating, characterized in that the aluminum coating is the above-mentioned aluminum coating, and the preparation method comprises the following steps: (1) Boron-modified phenolic resin, epoxy resin, aluminum powder, anticorrosive filler, anti-wear agent, binder, dispersant, anti-settling agent, adhesion promoter and organic solvent are mixed in proportion, and mechanically stirred at a speed of 1000-1500 r / min for 20-30 minutes to form a mixture A; (2) Add the lubricant, hygroscopic agent and thixotropic agent to the mixture A in proportion, and continue to mechanically stir at a speed of 1000-2000 r / min for 5-15 minutes to form a mixture B; (3) Add the mixture B into a grinder and grind it at a speed of 4500-5000 r / min for 30-90 minutes, and then filter to obtain the aluminum coating.

[0013] Optionally, the fineness of the filtration in step (3) is 50-75 μm.

[0014] On the other hand, the present application provides an application of a new chromium-free self-lubricating anti-corrosion aluminum coating, which is used to prepare a self-lubricating anti-corrosion aluminum coating on the surface of a fastener. The aluminum coating is the above-mentioned aluminum coating, or the aluminum coating prepared by the above-mentioned method.

[0015] Optionally, the steps for preparing the self-lubricating anti-corrosion aluminum coating include: (1) After sandblasting the surface of the fastener, clean it with an organic solvent; (2) Use nitrogen or air spray gun to evenly spray aluminum coating on the surface of fasteners; (3) After the coating is surface dry, it is cured at a temperature of 190±10℃ for 50-60 minutes to form a self-lubricating anti-corrosion aluminum coating.

[0016] The novel chromium-free self-lubricating anti-corrosion aluminum coating provided in this application, as well as its preparation method and application, realizes the preparation of the novel chromium-free self-lubricating anti-corrosion aluminum coating, and has the following beneficial effects compared with the prior art: (1) By compounding the components in a special proportion, not only is the chromium-free self-lubricating anti-corrosion aluminum coating provided by the present application obtained, the aluminum coating does not contain heavy metal chromium and meets environmental protection requirements, but the synergistic effect between the components makes the aluminum coating have good anti-corrosion, self-lubricating properties and bonding strength, which can significantly improve the service life and reliability of fasteners in complex environments.

[0017] (2) This application uses flaky aluminum powder and spherical aluminum powder of different fineness to work together, which not only avoids the problem of local agglomeration of the coating, but also further enhances the hardness and stability of the coating. The flaky aluminum powder has better film-forming properties. During the film-forming process, a portion of the flaky aluminum powder is in a parallel superposition, which significantly reduces the pores in the coating and makes the coating film more dense. At the same time, another portion of the flaky aluminum powder is filled between the coating particles, further improving the density and hardness of the coating, further exerting the barrier properties of the aluminum powder, blocking the contact between the corrosive medium and the fasteners, and enhancing the corrosion resistance of the coating.

[0018] (3) The preparation method of the new chromium-free self-lubricating anti-corrosion aluminum coating provided in this application is simple and quick, does not require high-temperature heating, reduces energy consumption, and saves production costs.

[0019] (4) First, the environmental performance of the aluminum coating provided by this application meets the high environmental standards required by the aviation field. Second, the anti-corrosion and self-lubricating functions of the aluminum coating significantly improve the corrosion resistance and assembly efficiency of fasteners. Finally, the stability and durability of the aluminum coating provide a strong guarantee for the safe operation of aircraft. In summary, the self-lubricating anti-corrosion aluminum coating of this application has broad application prospects and significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0021] Figure 1 A comparison chart of the friction coefficients of the aluminum coatings provided in Examples 1 to 3 of the present application and Comparative Examples 1 and 2; Figure 2 This is a comparison chart of the friction coefficients of the aluminum coatings provided in Examples 2, 4-6, and Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0022] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application are clearly and completely described below. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts also fall within the scope of protection of this application.

[0023] The present application provides a novel chromium-free self-lubricating anti-corrosion aluminum coating, which comprises the following components in percentage by weight: Boron-modified phenolic resin 20-40%, epoxy resin 1-6%, lubricant 7-30%, anti-wear agent 5-10%, moisture absorbent 2-5%, aluminum powder 5-20%, thixotropic agent 2-5%, anti-corrosion filler 5-10%, adhesion promoter 0.5-1.5%, anti-settling agent 1-2%, dispersant 1-2%, toughening agent 2-8%, balance organic solvent; The organic solvent includes ethanol and butanone in a weight ratio of 1:1-2.

[0024] Specifically, the boron-modified phenolic resin has a high heat resistance temperature and can increase the use temperature of the coating to 260°C. The epoxy resin has good adhesion and extremely low curing shrinkage. In this application, the boron-modified phenolic resin and the epoxy resin are mixed and used as the main film-forming components, which can effectively improve the strength and density of the aluminum coating and maintain good mechanical properties during the use of the coating. The lubricant provides good lubrication, and during the friction process, a friction transfer film is attached to the dual surfaces to reduce the friction coefficient. The wear-resistant agent increases the hardness of the coating, significantly enhances the wear resistance of the coating, and extends the service life. The desiccant can absorb moisture in the aluminum coating, prevent the aluminum coating from caking due to humidity changes during storage, maintain the fluidity of the coating, and help the coating maintain good uniformity. The toughening agent can improve the toughness of the coating, enhance the adhesion of the coating, and optimize the film-forming performance of the coating.

[0025] Aluminum powder has active chemical properties and acts as a sacrificial anode for cathodic protection. Anti-corrosion fillers can passivate the coating, further enhancing its corrosion resistance. Adhesion promoters can improve the coating's adhesion to fastener surfaces, enhancing its corrosion protection.

[0026] Preferably, the thixotropic agent is bentonite, the adhesion promoter is a silane coupling agent, such as one or more of A151 (vinyl triethoxysilane), A171 (vinyl trimethoxysilane), and A172 (vinyl tri(β-methoxyethoxy) silane), the anti-settling agent is BYK410, the dispersant is BYK P104s, and the toughening agent is polyvinyl butyral. The epoxy resin is E51 epoxy resin.

[0027] By compounding the components in a special proportion, not only is the chromium-free self-lubricating anti-corrosion aluminum coating provided in this application obtained, the aluminum coating does not contain heavy metal chromium and meets environmental protection requirements, but the synergistic effect between the components makes the aluminum coating have good anti-corrosion, self-lubricating properties and bonding strength, which can significantly improve the service life and reliability of fasteners in complex environments.

[0028] Optionally, the lubricant includes molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 2-10:5-20.

[0029] Specifically, molybdenum disulfide and polytetrafluoroethylene act as solid lubricants. Molybdenum disulfide can form a lubricating film on the surface of fasteners, significantly reducing the friction coefficient, thereby reducing the friction resistance of the fasteners during use, preventing jamming and biting, and at the same time forming a maze effect, improving corrosion resistance, and preventing rust and corrosion. Polytetrafluoroethylene (PTFE) also has excellent lubrication properties and is hydrophobic, which can significantly reduce the friction coefficient, prevent jamming and biting, and at the same time improve resistance to water vapor and improve anti-corrosion capabilities.

[0030] Optionally, the anti-wear agent is selected from Al2O3.

[0031] Specifically, Al2O3 has a higher hardness, thereby enhancing the wear resistance of the coating and extending its service life.

[0032] Preferably, the particle size of Al2O3 is selected to be 10-30nm. The appropriate particle size can fill the pores between the components and enhance the density of the coating. Optionally, the desiccant is acetic acid.

[0033] Optionally, the aluminum powder includes flake aluminum powder and spherical aluminum powder with a fineness of ≤10 μm, and the weight ratio of the flake aluminum powder to the spherical aluminum powder is 1:1-1.5.

[0034] Specifically, in the present application, the aluminum powder is selected from a mixture of flake aluminum powder and spherical aluminum powder. The flake aluminum powder has a two-dimensional structure, which improves the barrier property of the coating and further improves the anti-corrosion performance.

[0035] Furthermore, the fineness of the flaky aluminum powder is 1-5 μm, wherein the weight ratio of 1-2 μm flaky aluminum powder to 3-5 μm flaky aluminum powder is 1.6-2:1, and the weight ratio of flaky aluminum powder to spherical aluminum powder is 1:1-1.5.

[0036] Optionally, the anti-corrosion filler includes one or more of aluminum tripolyphosphate, aluminum dihydrogen tripolyphosphate, and zinc phosphate, which can improve the anti-corrosion performance of the coating and further delay the corrosion of the fastener.

[0037] On the other hand, the present application provides a method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating, wherein the aluminum coating is the above-mentioned aluminum coating, and the preparation method comprises the following steps: (1) Boron-modified phenolic resin, epoxy resin, aluminum powder, anticorrosive filler, anti-wear agent, binder, dispersant, anti-settling agent, adhesion promoter and organic solvent are mixed in proportion, and mechanically stirred at a speed of 1000-1500 r / min for 20-30 minutes to form a mixture A; (2) Add the lubricant, hygroscopic agent and thixotropic agent to the mixture A in proportion, and continue to mechanically stir at a speed of 1000-2000 r / min for 5-15 minutes to form a mixture B; (3) Add the mixture B into a grinder and grind it at a speed of 4500-5000 r / min for 30-90 minutes, and then filter to obtain the aluminum coating.

[0038] The present application realizes the preparation of a new chromium-free self-lubricating anti-corrosion aluminum coating through the above scheme. The boron-modified phenolic resin, epoxy resin, aluminum powder, anti-corrosion filler, wear agent, binder, dispersant, anti-settling agent, and adhesion promoter are dispersed in an organic solvent to form a mixture A. The lubricant, hygroscopic agent, and thixotropic agent are then added to the mixture A to form a mixture B. The components can be mixed evenly with each other, which is conducive to improving the uniformity of the aluminum coating. Finally, the components are further dispersed and mixed by high-speed grinding, which further improves the dispersion stability of the aluminum coating, thereby improving the stability of the coating and improving the self-lubricating and anti-corrosion properties of the fasteners.

[0039] Optionally, the fineness of the filtration in step (3) is 50-75 μm, which makes the coating smoother and denser and reduces defects.

[0040] On the other hand, the present application provides an application of a new chromium-free self-lubricating anti-corrosion aluminum coating, which is used to prepare a self-lubricating anti-corrosion aluminum coating on the surface of fasteners, including but not limited to bolts, nuts, and pipe clamps. The aluminum coating is the above-mentioned aluminum coating, or the aluminum coating prepared by the above-mentioned method.

[0041] Optionally, the steps for preparing the self-lubricating anti-corrosion aluminum coating include: (1) After sandblasting the surface of the fastener, clean it with an organic solvent; (2) Use nitrogen or air spray gun to evenly spray aluminum coating on the surface of fasteners; (3) After the coating is surface dry, it is cured at a temperature of 190±10℃ for 50-60 minutes to form a self-lubricating anti-corrosion aluminum coating.

[0042] Specifically, sandblasting removes oil and contaminants from the fastener surface and roughens the surface, facilitating coating adhesion. Furthermore, the surface roughness of the fastener after sandblasting reaches Ry = 10-20 μm, and the coating thickness is 5-13 μm. When using an organic solvent for cleaning, anhydrous ethanol is preferred.

[0043] The present invention will be described in further detail below in conjunction with the examples. However, it should be understood that these examples are intended to illustrate the present invention and are not intended to limit the scope of the invention. The experimental methods in the following examples, for which no specific conditions are specified, are generally measured according to national standards. If there are no corresponding national standards, the methods are carried out according to general international standards, conventional conditions, or according to the conditions recommended by the manufacturer. Unless otherwise stated, all parts are by weight, and all percentages are by weight.

[0044] Example 1 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: (1) According to weight percentage, 20% of boron-modified phenolic resin, 1% of E51 epoxy resin, 5% of aluminum powder, 5% of anticorrosive filler, 5% of anti-wear agent (Al2O3), 2% of toughening agent (polyvinyl butyral), 1% of dispersant (BYKp104s), 1% of anti-settling agent (BYK410), 0.5% of adhesion promoter (silane coupling agent) and the balance of organic solvent were mixed and mechanically stirred at a speed of 1000 r / min for 20 minutes to form a mixture A; The aluminum powder has a fineness of ≤10 μm, a weight ratio of flaky aluminum powder to spherical aluminum powder of 1:1, and a fineness of 1-5 μm aluminum flake powder, wherein the weight ratio of 1-2 μm aluminum flake powder to 3-5 μm aluminum flake powder is 1.6:1. The anti-corrosion filler is aluminum tripolyphosphate, and the organic solvent includes ethanol and butanone in a weight ratio of 1:1. The Al2O3 particle size is 10 nm.

[0045] (2) Add 7% of lubricant, 2% of hygroscopic agent (acetic acid) and 2% of thixotropic agent (bentonite) to mixture A by weight, and continue mechanically stirring at a speed of 1000 r / min for 5 minutes to form mixture B; The lubricant includes molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 2:5.

[0046] (3) Add mixture B into a grinder and grind at a speed of 4500 r / min for 30 minutes. After filtering, obtain aluminum coating.

[0047] Example 2 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: (1) According to weight percentage, 30% of boron-modified phenolic resin, 4% of E51 epoxy resin, 17% of aluminum powder, 7% of anticorrosive filler, 7% of wear-resistant agent (Al2O3), 5% of toughening agent (polyvinyl butyral), 1.5% of dispersant (BYKp104s), 1.5% of anti-settling agent (BYK410), 1% of adhesion promoter (silane coupling agent) and the balance of organic solvent were mixed and mechanically stirred at a speed of 1200 r / min for 25 minutes to form a mixture A; The aluminum powder has a fineness of ≤10 μm, a weight ratio of flaky aluminum powder to spherical aluminum powder of 1:1.2, and a fineness of flaky aluminum powder of 1-5 μm, with a weight ratio of 1.8:1 for 1-2 μm flaky aluminum powder to 3-5 μm flaky aluminum powder. The anti-corrosion filler is aluminum dihydrogen tripolyphosphate, and the organic solvent includes ethanol and butanone in a weight ratio of 1:1.5. The Al2O3 particle size is 20 nm.

[0048] (2) Add 17% of lubricant, 3% of hygroscopic agent (acetic acid) and 3.5% of thixotropic agent (bentonite) to mixture A by weight, and continue mechanically stirring at a speed of 1500 r / min for 10 minutes to form mixture B; The lubricant includes molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 5:15.

[0049] (3) Add mixture B into a grinder and grind at a speed of 4700 r / min for 60 minutes. After filtering, obtain aluminum coating.

[0050] Example 3 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: (1) According to weight percentage, 40% of boron-modified phenolic resin, 6% of E51 epoxy resin, 20% of aluminum powder, 10% of anticorrosive filler, 10% of wear-resistant agent (Al2O3), 8% of toughening agent (polyvinyl butyral), 2% of dispersant (BYKp104s), 2% of anti-settling agent (BYK410), 1.5% of adhesion promoter (silane coupling agent) and the balance of organic solvent were mixed and mechanically stirred at a speed of 1500 r / min for 30 minutes to form a mixture A; The aluminum powder has a fineness of ≤10 μm, a weight ratio of flaky aluminum powder to spherical aluminum powder of 1:1.5, and a fineness of 1-5 μm aluminum flake powder, with a weight ratio of 1-2 μm aluminum flake powder to 3-5 μm aluminum flake powder of 2:1. The anti-corrosion fillers are aluminum tripolyphosphate, aluminum dihydrogen tripolyphosphate, and zinc phosphate, and the organic solvents are ethanol and butanone in a weight ratio of 1:2. The Al2O3 particle size is 30 nm.

[0051] (2) Add 30% of lubricant, 5% of hygroscopic agent (acetic acid) and 5% of thixotropic agent (bentonite) to mixture A by weight, and continue mechanically stirring at a speed of 2000 r / min for 15 minutes to form mixture B; The lubricant includes molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 10:20.

[0052] (3) Add mixture B into a grinder and grind at a speed of 5000 r / min for 90 minutes. After filtering, obtain aluminum coating.

[0053] Comparative Example 1 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 2 is that: (1) According to weight percentage, 30% of boron-modified phenolic resin, 4% of E51 epoxy resin, 4.8% of aluminum powder, 4.8% of anticorrosive filler, 4.8% of wear-resistant agent (Al2O3), 1.9% of toughening agent (polyvinyl butyral), 0.9% of dispersant (BYKp104s), 0.9% of anti-settling agent (BYK410), 0.4% of adhesion promoter (silane coupling agent) and organic solvent were mixed and mechanically stirred at a speed of 1200 r / min for 25 minutes to form a mixture A; the amount of organic solvent was the same as that in Example 2.

[0054] (2) Add 6.9% of lubricant, 2% of hygroscopic agent (acetic acid) and 3.5% of thixotropic agent (bentonite) to mixture A by weight, and continue mechanically stirring at a speed of 1500 r / min for 10 minutes to form mixture B.

[0055] Comparative Example 2 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 2 is that: (1) According to weight percentage, 30% of boron-modified phenolic resin, 4% of E51 epoxy resin, 21% of aluminum powder, 11% of anticorrosive filler, 10.1% of wear-resistant agent (Al2O3), 10.1% of binder (polyvinyl butyral), 2.1% of dispersant (BYKp104s), 2.1% of anti-settling agent (BYK410), 1.6% of adhesion promoter (silane coupling agent) and organic solvent were mixed and mechanically stirred at a speed of 1200 r / min for 25 minutes to form a mixture A; the amount of organic solvent was the same as that in Example 2.

[0056] (2) Add 31% of lubricant, 6% of hygroscopic agent (acetic acid) and 3.5% of thixotropic agent (bentonite) to mixture A by weight, and continue mechanically stirring at a speed of 1500 r / min for 10 minutes to form mixture B.

[0057] Experimental Example 1 Anti-corrosion performance test The aluminum coatings provided in Examples 1 to 3 and Comparative Examples 1 and 2 are sprayed on the surface of the substrate to obtain a self-lubricating anti-corrosion aluminum coating.

[0058] Spraying process: After sandblasting the substrate surface, clean it with anhydrous ethanol; use a nitrogen spray gun to evenly spray the aluminum coating on the substrate surface; after the coating is surface-dried, cure it at a temperature of 190±10℃ for 50-60 minutes to form a self-lubricating anti-corrosion aluminum coating with a thickness of 5-13μm.

[0059] Experimental Example 1.1 Neutral salt spray resistance time test method: According to the national standard GB / T 1771-2007 "Paints and varnishes, determination of resistance to neutral salt spray", each test group was set up with 3 parallel tests, and the average value was taken. The test results are shown in Table 1.

[0060] Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Neutral salt spray resistance time / h 1800 2000 2000 1000 1100 Experimental Example 1.2 The corrosion resistance of the self-lubricating anti-corrosion aluminum coatings provided in Examples 1 to 3 and Comparative Examples 1 and 2 was tested using the acetic acid salt spray test and alternating immersion test methods in the NAS 4006:2014 "Aluminum Coating" standard compiled by the American National Aeronautic Standards Committee.

[0061] Specific operation: The substrate coated with self-lubricating anti-corrosion aluminum coating is exposed to the acetic acid spray test for 14 days: a) The pH value of the acetic acid solution is maintained in the range of 3.0-3.1. b) The tilt angle of the specimen should be 45° to the vertical direction. The air flow is discharged directly into the cabinet at regular intervals and the following continuous cycle is allowed: 4 6-hour cycles per day, each cycle includes: (1) 45 minutes of spraying period. (2) 2 hours of direct air purge (drying cycle). (3) Soak for 3 hours and 15 minutes at a relative humidity of 45 to 90% and 95°F. After the test, observe whether there are obvious signs of corrosion on the coating surface.

[0062] As can be seen from Table 1, the self-lubricating anti-corrosion aluminum coatings provided in Examples 1 to 3 of the present application have good corrosion resistance. At the same time, the corrosion conditions of the self-lubricating anti-corrosion aluminum coating surfaces tested by the NAS 4006:2014 "Aluminum Coating" standard in Experimental Example 1.2 were observed. No obvious corrosion marks were observed on the coating surfaces of Examples 1 to 3, while corrosion spots were present on the test coating surfaces of Comparative Example 1 and Comparative Example 2. This shows that by compounding the components in the aluminum coating in a special ratio, the components work synergistically to form a dense and stable coating on the substrate surface, which can effectively prevent galvanic corrosion, block the contact between the substrate and the external environment, and provide long-term protection for parts such as titanium alloy fasteners.

[0063] Experimental Example 2 Self-lubricating performance test The aluminum coatings provided in Examples 1 to 3 and Comparative Examples 1 and 2 were sprayed on the surface of the substrate using the method of Experimental Example 1 to obtain a self-lubricating anti-corrosion aluminum coating.

[0064] Test method: Using ASTM G99 standard, the friction coefficient of the self-lubricating anti-corrosion aluminum coating provided by Examples 1 to 3 and Comparative Examples 1 and 2 was tested. Each test group was set up with 3 parallel tests and the average value was taken. The test results are shown as follows: Figure 1 shown.

[0065] observe Figure 1 As can be seen, the friction coefficients of the self-lubricating, anti-corrosion aluminum coatings provided in Examples 1-3 of the present application are significantly lower than those in Comparative Examples 1 and 2. The components of the aluminum coatings are mixed in a specific ratio and interact with each other to form a barrier layer with both anti-corrosion and lubricating properties on the substrate surface. Furthermore, the addition of lubricants and aluminum powder to the aluminum coatings improves the coating's corrosion resistance while also providing superior lubrication during use.

[0066] Experimental Example 3 Adhesion test The aluminum coatings provided in Examples 1 to 3 and Comparative Examples 1 and 2 were sprayed on the surface of the substrate using the method of Experimental Example 1 to obtain a self-lubricating anti-corrosion aluminum coating, and an adhesion test was performed.

[0067] Experimental Example 3.1 The adhesion of aluminum coatings was tested according to the standard GB / T 5210-2006, "Paints and varnishes adhesion test by pull-off method." Three replicates were run for each test, and the average results were calculated. The results are shown in Table 2.

[0068] Table 2 Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Adhesion / Mpa 8.5 8.6 9.0 6.5 6.7 Experimental Example 3.2 Using the test method in the NAS 4006:2014 "Aluminum Coating" standard compiled by the American Institute of Aeronautics and Astronautics, the substrate coated with the self-lubricating anti-corrosion aluminum coating was clamped in a vise and the test part was bent back and forth until it broke. The coating condition of the broken end surface was inspected under a 4x magnifying glass to determine whether the adhesion of the self-lubricating anti-corrosion aluminum coating met the standard.

[0069] As clearly shown in Table 2, the self-lubricating, anti-corrosion aluminum coatings provided in Examples 1-3 all exhibited superior adhesion compared to Comparative Examples 1 and 2. Furthermore, coating adhesion was tested using the method of Experimental Example 3.2. Examination of the coating at the fractured end surface under a 4x magnifying glass revealed that the coatings provided in Examples 1-3 exhibited no separation from the base metal at the fractured end surface or elsewhere. However, observation of the fractured end surfaces of Comparative Examples 1 and 2 revealed varying degrees of delamination at the edges and other locations of the coatings, with the separation between the coating and the base metal being particularly severe at the cross-section. This demonstrates that the adhesion of Examples 1-3 is superior to that of Comparative Examples 1 and 2, meeting the requirements of NAS 4006:2014, "Aluminum Coatings."

[0070] Combined with the results of Experimental Examples 3.1 and 3.2, it is shown that by adopting the proportions between the components in the aluminum coating provided in this application, the adhesion of the aluminum coating can be greatly improved, thereby promoting the strength of the coating, delaying or avoiding the erosion of fasteners by external corrosive media, thereby improving the reliability of the fasteners and extending the service life of the fasteners.

[0071] Example 4 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 2 is that: In step (1), the aluminum powder includes flake aluminum powder and spherical aluminum powder in a weight ratio of 1:1, the fineness of the spherical aluminum powder is 3 μm, and the weight ratio of 1-2 μm flake aluminum powder to 2-3 μm flake aluminum powder is 1.6:1.

[0072] Example 5 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 2 is that: In step (1), the aluminum powder includes flake aluminum powder and spherical aluminum powder in a weight ratio of 1:1.2, the fineness of the spherical aluminum powder is 4 μm, and the weight ratio of 1-2 μm flake aluminum powder to 2-3 μm flake aluminum powder is 1.8:1.

[0073] Example 6 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 2 is that: In step (1), the aluminum powder includes flake aluminum powder and spherical aluminum powder in a weight ratio of 1:1.5, the fineness of the spherical aluminum powder is 2 μm, and the weight ratio of 1-2 μm flake aluminum powder to 2-3 μm flake aluminum powder is 2:1.

[0074] Comparative Example 3 A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating comprises the following steps: The difference from Example 5 is that: No aluminum powder is added in step (1).

[0075] Experimental Example 4 Anti-corrosion performance test The aluminum coatings provided in Example 2, Example 4 to Example 6 and Comparative Example 3 were sprayed on the surface of the substrate using the method of Experimental Example 1 to obtain a self-lubricating anti-corrosion aluminum coating.

[0076] Experimental Example 4.1 Neutral Salt Spray Resistance Time Test Method: According to the national standard GB / T 1771-2007 “Paints and varnishes, determination of resistance to neutral salt spray”, three parallel tests were set up for each test group, and the average value was taken. The test results are shown in Table 3.

[0077] Table 3 Example 2 Example 4 Example 5 Example 6 Comparative Example 3 Neutral salt spray resistance time / h 2000 2450 2530 2480 720 Experimental Example 4.2 The same method as that of Experimental Example 1.2 was used to test the anti-corrosion performance of the self-lubricating anti-corrosion aluminum coatings provided in Example 2, Example 4-Example 6 and Comparative Example 3.

[0078] As shown in Table 3 of Experimental Example 4.1, Examples 4-6 exhibit superior corrosion resistance compared to Example 2. Comparative Example 3 exhibits the shortest neutral salt spray resistance and the worst corrosion resistance. Experimental Example 4.2 also observed corrosion on the surfaces of the self-lubricating, anti-corrosion aluminum coatings of Examples 2, 4-6, and Comparative Example 3. No obvious signs of corrosion were observed on the surfaces of the coatings of Examples 2 and 4-6, while corrosion spots were observed on the surface of the coating of Comparative Example 3.

[0079] It is explained that by using flake aluminum powder and spherical aluminum powder, and matching flake aluminum powder of different fineness with spherical aluminum powder, aluminum powders of different shapes and finenesses can work synergistically with each other, and a part of the flake aluminum powders are stacked in parallel, which significantly reduces the pores in the coating and makes the coating film more dense. At the same time, another part of the flake aluminum powder is filled between the spherical aluminum powder and other coating components, further improving the density and hardness of the coating, further exerting the barrier performance of the aluminum powder, blocking the contact of corrosive media with fasteners, and enhancing the stability and corrosion resistance of the coating.

[0080] Experimental Example 5 Self-lubricating performance test The friction coefficient of the self-lubricating anti-corrosion aluminum coating provided in Example 2, Example 4-Example 6 and Comparative Example 3 was tested using the test method of Experimental Example 2. Three parallel tests were conducted in each test group, and the average value was taken. The test results are shown in Figure 2. Figure 2 shown.

[0081] Depend on Figure 2 It can be seen that by using flaky and spherical aluminum powders, and by mixing flaky and spherical aluminum powders of varying fineness, the self-lubricating properties of the aluminum coatings provided in Examples 4-6 are further enhanced compared to Example 2. This reduces wear on fasteners during use, thereby extending the service life of the fasteners. It also significantly reduces installation and removal torques, improving assembly efficiency.

[0082] Experimental Example 6 Durability testing Paint stripper resistance test: At room temperature (23.9±2.8°C), the self-lubricating, anti-corrosion aluminum coatings provided in Examples 2, 4-6, and Comparative Example 3 were immersed in a paint stripper for 24 hours. The stripper was removed with tap water and dried to constant weight. The aluminum coatings were then tested for adhesion and pencil hardness, and the surface of the aluminum coatings was observed for blistering. The paint stripper used was the paint stripper specified in TT-R-2918.

[0083] Aviation kerosene resistance test: At (65.6±2.7)°C, the self-lubricating, anti-corrosion aluminum coatings provided in Examples 2, 4-6, and Comparative Example 3 were immersed in RP-3 aviation kerosene for 720 hours. The aviation kerosene was then washed off with anhydrous ethanol and dried to a constant weight. The aluminum coatings were then tested for adhesion and pencil hardness, and the presence of blistering was observed.

[0084] Adhesion test: The test method of Experimental Example 3.1 was used.

[0085] Pencil hardness test: GB / T 6739-2022 "Paints and varnishes - Determination of film hardness by pencil method." Three parallel tests were conducted in each test group, and the average value was taken. The test results are shown in Table 4.

[0086] Table 4 Table 4 shows that Examples 4-6 exhibit excellent adhesion and durability, resisting paint strippers and aviation kerosene without deterioration and demonstrating excellent durability. In Examples 2, 4-6, and 6, no blistering occurred on the coating surfaces after immersion in paint strippers and aviation kerosene. However, the decrease in adhesion in Example 2 was significantly greater than that in Examples 4-6, and the pencil hardness of Examples 4-6 remained unchanged. This demonstrates that the use of flaky and spherical aluminum powders, and the mixing of flaky and spherical aluminum powders of varying fineness, significantly improved the adhesion and durability of the aluminum coating.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some or all of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A new type of chromium-free self-lubricating anti-corrosion aluminum coating, characterized in that: The aluminum coating comprises the following components in percentage by weight: Boron-modified phenolic resin 20-40%, epoxy resin 1-6%, lubricant 7-30%, anti-wear agent 5-10%, moisture absorbent 2-5%, aluminum powder 5-20%, thixotropic agent 2-5%, anti-corrosion filler 5-10%, adhesion promoter 0.5-1.5%, anti-settling agent 1-2%, dispersant 1-2%, toughening agent 2-8%, balance organic solvent; The organic solvent comprises ethanol and butanone in a weight ratio of 1:1-2.

2. The novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 1 is characterized in that: The lubricant comprises molybdenum disulfide and polytetrafluoroethylene in a weight ratio of 2-10:5-20.

3. The novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 1 is characterized in that: The anti-wear agent is selected from Al2O3.

4. The novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 1 is characterized in that: The desiccant is acetic acid.

5. The novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 1 is characterized in that: The aluminum powder includes flaky aluminum powder with a fineness of ≤10 μm and spherical aluminum powder, and the weight ratio of the flaky aluminum powder to the spherical aluminum powder is 1:1-1.

5.

6. The novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 5 is characterized in that: The anti-corrosion filler includes one or more of aluminum tripolyphosphate, aluminum dihydrogen tripolyphosphate and zinc phosphate.

7. A method for preparing a novel chromium-free self-lubricating anti-corrosion aluminum coating, characterized in that: The aluminum coating is the aluminum coating according to any one of claims 1 to 6, and the preparation method comprises the following steps: (1) The boron-modified phenolic resin, the epoxy resin, the aluminum powder, the anticorrosive filler, the anti-wear agent, the binder, the dispersant, the anti-settling agent, the adhesion promoter, and the organic solvent are mixed in proportion, and mechanically stirred at a speed of 1000-1500 r / min for 20-30 minutes to form a mixture A; (2) adding the lubricant, the hygroscopic agent and the thixotropic agent to the mixture A in proportion, and continuing to mechanically stir at a speed of 1000-2000 r / min for 5-15 minutes to form a mixture B; (3) Add the mixture B into a grinder, grind at a speed of 4500-5000 r / min for 30-90 minutes, and obtain the aluminum coating after filtering.

8. The method for preparing the novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 7, characterized in that: The fineness of the filtration in step (3) is 50-75 μm.

9. Application of a new type of chromium-free self-lubricating anti-corrosion aluminum coating, characterized in that: The aluminum coating is used to prepare a self-lubricating anti-corrosion aluminum coating on the surface of a fastener. The aluminum coating is the aluminum coating described in any one of claims 1 to 6 above, or the aluminum coating prepared by the method described in claim 7 or 8 above.

10. The use of the novel chromium-free self-lubricating anti-corrosion aluminum coating according to claim 9, characterized in that: The preparation steps of the self-lubricating anti-corrosion aluminum coating include: (1) After sandblasting the surface of the fastener, it is cleaned with an organic solvent; (2) using a nitrogen or air spray gun to evenly spray the aluminum coating onto the surface of the fastener; (3) After the coating is surface dry, it is cured at a temperature of 190±10℃ for 50-60 minutes to form a self-lubricating anti-corrosion aluminum coating.